Effect of gamma radiation on the developmental stages of Necrobia rufipes (deGeer) infesting stored dried fishes (University Journal of Zoology, Rajshahi University, 2007)
Key words: Gamma radiation; dried fish; Necrobia rufipes; immature stages Univ. j. zool. Rajshahi Univ. Vol.23, 2004. pp. 61-64